Research on the Construction of a Cognitive-Psychological Adaptation System for Digital Teaching Empowered by Healing Design - Cheng, Meishan (Pinnacle Academic Press Proceedings Series, 2026)
This study constructs a cognitive-psychological adaptation system for digital teaching centered on healing design to address students' mental health and learning efficiency in the contemporary educational environment. By combining theoretical analysis with empirical research, it explores how to integrate healing design concepts into the digital teaching process to improve students' learning motivation and emotional engagement. The research framework clarifies the mechanisms through which healing-oriented visual, spatial, and interactive elements in digital platforms can regulate learners’ cognition, emotion, and behavior. Quantitative and qualitative data are used to examine changes in students’ anxiety, stress, and perceived support, as well as their attention, persistence, and satisfaction with learning tasks. The results show that healing design can effectively enhance students' learning experience, reduce anxiety and stress, promote positive emotions, and further improve learning outcomes. In addition, the study identifies key design principles, such as emotional safety, cognitive load balance, and supportive feedback, which contribute to a more adaptive digital learning environment. These findings provide theoretical support and practical guidance for optimizing digital teaching and introduce the concept of psychological adaptation into teaching design, moving toward a more humanized, inclusive, and effective educational model that better responds to the psychological needs of diverse learners in digital contexts.